2017
DOI: 10.2147/ott.s104767
|View full text |Cite
|
Sign up to set email alerts
|

Arenobufagin activates p53 to trigger esophageal squamous cell carcinoma cell apoptosis in vitro and in vivo

Abstract: Esophageal squamous cell carcinoma (ESCC) is often diagnosed at late incurable stage and lacks effective treatment strategy. Bufadienolides are cardiotonic steroids isolated from the skin and parotid venom glands of the toad Bufo bufo gargarizans Cantor with novel anticancer activity. However, there is little information about the effects and action mechanisms of bufadienolides on ESCC cells. In this study, the in vitro and in vivo anti-ESCC activities of bufadienolides, including bufalin (Bu) and arenobufagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…e researchers established a nude mouse model with xenograft transplantation of A549 tumor and confirmed that cinobufotalin inhibits tumor growth through regulation of the nonapoptotic death pathway of cyclophilin-D in lung cancer cells [27,28]. Arenobufagin, a cardiac glycoside extracted from toad skin, activates caspase-mediated apoptosis of esophageal cancer cells through exogenous and endogenous pathways [29]. e authors of this previous study have also confirmed that arenobufagin exerts good antivascular effect and blocks the migration and invasion of human umbilical vein endothelial cells by inhibiting the expression of VEGF [30].…”
Section: Discussionmentioning
confidence: 92%
“…e researchers established a nude mouse model with xenograft transplantation of A549 tumor and confirmed that cinobufotalin inhibits tumor growth through regulation of the nonapoptotic death pathway of cyclophilin-D in lung cancer cells [27,28]. Arenobufagin, a cardiac glycoside extracted from toad skin, activates caspase-mediated apoptosis of esophageal cancer cells through exogenous and endogenous pathways [29]. e authors of this previous study have also confirmed that arenobufagin exerts good antivascular effect and blocks the migration and invasion of human umbilical vein endothelial cells by inhibiting the expression of VEGF [30].…”
Section: Discussionmentioning
confidence: 92%
“…Cellular proliferation and cell cycle are regulated by regulating MDM2/P53 signaling in esophageal squamous cell carcinoma [34]. In the study of isoleucine anti-esophageal squamous cell carcinoma, it was found that iso-valine can inhibit tumor growth by activating the p53 pathway [35]. Zuev et al [36] studied the insulin levels and islet β-cell morphology changes in 27 patients with esophageal cancer after one-stage esophagectomy and gastric pedicle graft repair.…”
Section: Discussionmentioning
confidence: 99%
“…Toad venom has been widely used in China as a local anesthetic, cardiotonic, antimicrobial, and antineoplastic agent for many years [ 26 , 27 ]. Arenobufagin, as one of the main biologically active compounds extracted from toad venom, has been showed to exhibit potential anti-cancer effects in human hepatocellular carcinoma (HCC), esophageal squamous cell carcinoma and cervical carcinoma cells [ 19 , 21 , 22 ]. However, the anti-NSCLC effects of arenobufagin are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Deng et al found that arenobufagin could intercalate with DNA to induce G2 cell cycle arrest through the ATM/ATR pathway in HCC cells [ 20 ]. Except in HCC, arenobufagin has also been shown to inhibit growth and induce apoptosis in human esophageal squamous cell carcinoma cells and cervical carcinoma cells [ 21 , 22 ]. However, the effects and mechanisms of arenobufagin on lung cancer are still not clear.…”
Section: Introductionmentioning
confidence: 99%